A Multicomponent Library Resource Model to Enhance Academic Global Health Education Among Residency Programs. Issue 2 (3rd April 2017) - Patel, Rupa R.; Ravichandran, Sandhiya; Doering, Michelle M.; Hardi, Angela C.
ABSTRACT: Global health is becoming an increasingly important component of medical education. Medical libraries have an opportunity to assist global health residents with their information needs, but first it is important to identify what those needs are and how best they can be addressed. This article reports a collaboration between global health faculty and an academic medical librarian to assess the information needs of global health pathway residents and how assessment data are used to create a multicomponent program designed to enhance global health education.